Accidentally dating his boss - Lynn, Kristine (Harlequin medical romance., 2024)
Plastic surgeon to the stars, Dr. Owen, is not happy with his new boss's ideas. And it doesn't help that Dr. Kris is infuriatingly stunning! Thankfully, Owen has @ladydoc to vent to. He doesn't have space in his life for dating, but the anonymity of their virtual relationship protects them both. Yet, when Owen discovers the unthinkable--that Kris is his cyber crush!--will he be brave enough to bring their accidental connection offline ?